Effects of a transient lack of dietary mineral phosphorus on renal gene expression and plasma metabolites in two high-yielding laying hen strains - Hiba Qasir; Henry Reyer; Michael Oster; Siriluck Ponsuksili; Nares Trakooljul; Vera Sommerfeld; Markus Rodehutscord; Klaus Wimmers (BMC Genomics)
Abstract Background There is an emerging body of evidence that current poultry feed is formulated in excess for phosphorus (P), which results in unnecessarily high P excretions. Sustainable concepts for agricultural P flows should trigger animal-intrinsic mechanisms for efficient P utilization. In the current study, Lohmann Brown (LB) and Lohmann Selected Leghorn (LSL) laying hens were fed either a high P diet (P+) with 1 g/kg mineral P supplement or a low P diet (P-) with 0 g/kg mineral P supplement for a period of 4 weeks prior to sampling. Before and after onset of laying, i.e., at 19 and 24 weeks of life, kidney and plasma samples were collected to investigate the endogenous P utilization in response to restricted dietary P, laying hen strain, and sexual maturation. Results Plasma analyses of minerals and metabolites confirmed the response to a low P diet, which was characterized by a significant reduction in plasma P levels at week 19 in both strains. The plasma calcium (Ca) levels were tightly regulated throughout the entire experimental period. Notably, there was a numerical trend of increased plasma calcitriol levels in P- fed birds of both strains compared to the P + group, which might have mediated a substantial role regarding the adaptive responses to low P supply. At week 19, RNA sequencing of kidney identified 1,114 and 556 differentially expressed genes (DEGs) unique to the LB and LSL strains, respectively. The number of DEGs declined with increasing maturity of the hens culminating in 90 and 146 DEGs for LB and LSL strains at week 24. Analyses revealed an enrichment of pathways related to energy metabolism and cell cycle, particularly at week 19 in both strains. The diet-specific expression of target genes involved in P homeostasis highlighted transcripts related to active (SLC34A1, SLC20A2) and passive mineral transport (CLDN14, CLDN16), Ca utilization (STC1, CALB1), and acid-base balance (CA2, SLC4A1). Conclusions Results suggest that both laying hen strains adapted to the lack of mineral P supplements and achieved a physiological Ca: P-ratio in body compartments through endogenous regulation as evidenced via the endocrine profile.